Observation of Extensive Chromosome Axis Remodeling during the “Diffuse-Phase” of Meiosis in Large Genome Cereals - Colas, Isabelle; Darrier, Benoit; Arrieta, Mikel; Mittmann, Sybille U.; Ramsay, Luke; Sourdille, Pierre; Waugh, Robbie (Frontiers in Plant Science, 2017)
The production of balanced fertile haploid gametes requires the faithful separation of paired (synapsed) chromosomes towards the end of meiotic prophase I (desynapsis). This involves the timely dissolution of the synaptonemal complex during the pachytene-diplotene transition, a stage traditionally referred to as the ‘diffuse stage’. In species with large genomes such as barley (Hordeum vulgare L.) and wheat (Triticum aestivum L.) we know most about the early stages of meiotic prophase I. There, synapsis initiates at the telomeric ends of chromosomes and progresses towards the centromeric regions through the ordered assembly of the synaptonemal complex (SC). Synapsis is impacted by recombination (crossing over, CO) which locally modifies the extent of chromatin compaction and extension. CO is uneven along the chromosomes, occurring mainly towards the telomeric regions resulting in a highly skewed distribution of recombination events. However, we know very little about the process of desynapsis which occurs during the ‘diffuse stage’, where the synapsed and recombined chromosomes faithfully desynapse and separate into daughter cells. Here, using 3D-SIM super-resolution immuno-cytology combined with the use of antibodies directed against two crucial SC proteins, ASY1 and ZYP1, we followed the whole of meiosis I (i.e. both synapsis and desynapsis) in both barley and wheat. We showed that synapsis forms a characteristic tri-partite SC structure in zygotene (more clearly seen in barley). Towards the end of meiosis I, as the SC starts to disassemble, we show that extensive chromosome axis remodelling results in the formation of characteristic ‘tinsel-like’ structures in both wheat and barley. By using a mutant (des10) that is severely compromised in polymerization of ZYP1during synapsis, we show that tinsel structure formation during SC dissolution is not dependant on full synapsis and may relate instead to changes in expansion stress. Our observations highlight a potentially new role for ASYNAPSIS1 (ASY1) in desynapsis, in addition to chromosome synapsis and cohesion.